Computational modeling of high‐level cognition and brain function - Just, Marcel Adam (Hum Brain Mapp, 1999)
This article describes a computational modeling architecture, 4CAPS, which is consistent with key properties of cortical function and makes good contact with functional neuroimaging results. Like earlier cognitive models such as SOAR, ACT‐R, 3CAPS, and EPIC, the proposed cognitive model is implemented in a computer simulation that predicts observable variables such as human response times and error patterns. In addition, the proposed 4CAPS model accounts for the functional decomposition of the cognitive system and predicts fMRI activation levels and their localization within specific cortical regions, by incorporating key properties of cortical function into the design of the modeling system. Hum. Brain Mapping 8:128–136, 1999. © 1999 Wiley‐Liss, Inc.